PERUBAHAN KAPASISTAS PENYERAPAN TENAGA KERJA DI SEKTOR INFORMAL - Hans-Dieter Evers (Populasi, 1993)
Employment in the informal sector has risen sharply until about 1980, but has sice started to decline. This is also true for employment in trade, which accounts for the mayor part of informal sector employment. On the basis of data derived from a survey in informal sector trade in Central Java it is shown that the informal sector is increasingly formalized. Consequently the labor absorption capacity of informal sector trade has declined. It will be necessary to take account of this fact in formulating employment targets for the next Indonesian development plan REPELITA VI.